중국 기공 및 쿤달리니 요가 명상이 숙련자의 심박변이율(HRV) 변화에 미치는 영향에 관한 연구 - 장대근; 장재근; 박승훈; 한민수; Jang, Dae-Geun; Jang, Jae-Keun; Park, Seung-Hun; Hahn, Minsoo (Journal of biomedical engineering research, 2012)
In this paper, we have investigated effects of two specific meditations (Chinese qigong meditation and Kundalini yoga meditation) on the heart rate variability (HRV), which is a well-known quantitative measure of autonomic balance, of skilled students. To analyze the effects, the MIT/BIH physionet database was utilized. The database includes RR intervals of eight skilled Chinese qigong meditators (5 women and 3 men; age range 26-35) and four skilled Kundalini yoga meditators (2 women and 2 men; age range 20-52). RR intervals of each subject were measured before and during the meditations. For HRV analysis, we have used typical four HRV parameters - the low frequency to high frequency power ratio (LF/HF ratio), SD2/SD1 ratio, sample entropy, and fractal dimension. The LF/HF ratio was calculated by the autoregressive spectrum and the SD2/SD1 ratio was derived from the Poincar$\grave{e}$ plot. The sample entropy was computed from the phase space plot and the fractal dimension was estimated by the Higuchi's algorithm. In the experiments, the Wilcoxon signed rank test was employed because we used small datasets and compared HRV parameters before and during the meditations. As a result, we have found increment of the LF/HF and SD2/SD1 ratios in both meditations; whereas the sample entropy is decreased during the meditations. In addition, the fractal dimension is increased during the Chinese qigong meditation; whereas it is decreased during the Kundalini yoga meditation. The results show that the sympathetic nervous system is generally more activated in skilled Chinese qigong and Kundalini yoga meditators, but the activation of the parasympathetic nervous tone is suppressed.